2017
DOI: 10.1016/j.joca.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Subregional laminar cartilage MR spin–spin relaxation times (T2) in osteoarthritic knees with and without medial femorotibial cartilage loss – data from the Osteoarthritis Initiative (OAI)

Abstract: Objective To explore whether subregional laminar femorotibial cartilage spin-spin relaxation time (T2) is associated with subsequent radiographic progression and cartilage loss and/or whether one-year change in subregional laminar femorotibial cartilage T2 is associated with concurrent progression in knees with established radiographic OA (ROA). Methods In this case-control study, Osteoarthritis Initiative (OAI) knees with medial femorotibial progression were selected based on one-year loss in both quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
2
14
2
Order By: Relevance
“…Whole‐joint scoring systems have partly emerged due to the large database of clinical and imaging information collected from imaging human subjects. The Osteoarthritis Initiative (https://oai.epi-ucsf.org/), a nationwide multicentre group, collected this information and follow‐up data . Their aim is to create a public domain where these data are accessible to researchers and are used as a resource for clinical research.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Whole‐joint scoring systems have partly emerged due to the large database of clinical and imaging information collected from imaging human subjects. The Osteoarthritis Initiative (https://oai.epi-ucsf.org/), a nationwide multicentre group, collected this information and follow‐up data . Their aim is to create a public domain where these data are accessible to researchers and are used as a resource for clinical research.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…2). 56,[58][59][60][61] The most superficial zone, the lamina splendens, also has very short values, with the collagen being parallel to the tidemark. This layer may be seen with sufficient spatial resolution of gray scale imaging but is often beyond the resolution of parametric mapping techniques as a separate region of interest.…”
Section: T2 Relaxometrymentioning
confidence: 99%
“…54 Recent T2 relaxometry studies of cartilage within patients post ACL-reconstruction (ACL-R) have identified associations between longitudinal progression of cartilage T2 relaxation times and cartilage pathology. 31,34,51,52,65,66 Additionally, laminar analyses of cartilage T2 values after ACL-injury have demonstrated disparate changes between the superficial and deep layers of the cartilage 58,60,65 A recent study by Williams et al also reported that early changes in T2 metrics at 6-month follow-up were correlated with changes in cartilage thickness and T2 at 2-year followups after ACL-R. 31 As T2 relaxation within the deep and calcified cartilage layers exhibit the faster T2 decay in comparison to more superficial layers, standard T2 mapping techniques can be limited in their ability to capture these data and therefore imperfect in its assessments of the deeper layers of articular cartilage 53,67,68 However, multiecho ultra-short echo time (UTE) MRI is well suited for the evaluation of these short T2 relaxation times as they have very small (ultra-short) delays between excitation and data acquisition. 40,53 UTE MRI techniques have therefore effectively been used to increase SNR in the short T2 tissues of the knee, including the deep layers of knee cartilage.…”
Section: T2 Relaxometrymentioning
confidence: 99%
“…The study included participants that were previously selected for investigating the association between thigh anatomical muscle cross-sectional areas with structural knee OA progression [19]. In brief, OAI knees with and without medial structural progression were selected from a sample of 725 OAI participants with longitudinal data on change in cartilage thickness obtained from 3 Tesla MRI [20] and in radiographic joint space width (JSW) obtained from fixedflexion radiography [21] as described previously [19,22]. Cartilage thickness change was assessed from a double oblique coronal fast low angle shot (FLASH) MRI sequence that was acquired in the right knees of the OAI participants [19,20], who were graded as Kellgren & Lawrence grade (KLG) 2-4 according to the site radiographic readings [23].…”
Section: Study Design and Sample Selectionmentioning
confidence: 99%